PENGARUH METODE FONIK BERBANTUAN MEDIA FLASH CARD TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS RENDAH SD INPRES MOROWA - Mujahida, Nur Aenatul; Fatimah, Waddi; Khaedar, Muh.; Satriawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of the phonics method assisted by flash card media on the beginning reading ability of lower grade students of SD Inpres Morowa. This study is an experimental research type. The sample in this study were all grade I students, with a total of 32 students. The research instruments used were observation sheets, reading ability tests and documentation. With data analysis techniques using SPSS 30.0. based on the results of descriptive analysis and inferential statistical analysis, where the teacher's activity in implementing the phonics method assisted by flash card media obtained an average value of 3.4 which means it was implemented well, then the results of the analysis of student activities obtained an average value of 3.3 which means it was implemented well. The results of the prerequisite test, namely the normality test, obtained a P-Value pretest = 0.535 which means the data is normally distributed, then the results of the homogeneity test obtained a P-Value = 0.541 which means homogeneity is met. The results of the hypothesis test obtained a value of 0.000 which is smaller than the significance level of 0.05, which means that there is a difference in students' reading ability, so H0 is rejected and H1 is accepted. Based on the results of the research that has been conducted, it can be concluded that the phonics method assisted by flash card media has an effect on the initial reading ability of lower grade students at SD Inpres Morowa.